Pendekatan Hukum Islam terhadap Jihad dan Terorisme - Lukman Arake (Universitas Islam Negeri Mataram, 2012)
There is a presumption of some circles of non-Muslims that Muslims are the spreader of terrors and terrorism throughout the world through the implementation of the concept of jihād. This assumption seemed to be justified the emerging terrorism cases involving Muslim actors, such as suicide bombings. This paper aims to clarify the issue by critically scrutinizing the true meaning of jihād rooted both in the holy book the al-Qur’an and sunnah of the Prophet Muhammad. Socio-historical approach is applied to better understand the holistic context of the meaning of jihād concept in both sources of Islamic teachings. The author concludes that the presumption is a misconception resulting from ignorance of certain parties about the true meaning of jihād in Islam. There is also a possibility that the misunderstanding is intentional, because the motives of abusing the dignity of Islamic teachings, especially about jihād.